Kinetics and Mechanism of hydrolysis of Di-Ethyl Dithiophosphate in Acid Media - Patil, R.; Shinde, C.P.; Samadhia, A. (Asian Journal of Chemistry, 2010)
Investigation of diethyl-dithio phosphate was carried out by using "Allen's" modified method of colorimetry, in aqueous medium from 0.1 to 7.0 mol dm–3 HCl at 98ºC. Ionic strength data exhibit different contribution of neutral species and presence of acid catalysis. Theoretical rates estimated from 2nd empirical term of Debye-Hückel equation have been found in close agreement with experimental rates. Ionic strength, temperature, solvent and concentration of kinetic studies are provided to identify the reactive species and molecularity. Molecularity and bond fission are also discussed in terms of Zücker-Hammett hypothesis. Hammett acidity functions, Bünnet and Bünnett-Olsen parameters and isokinetic relationship.